Envisioning Higher Education: How Imagining the Future Shapes the Implementation of a New Field in Higher Education - Saner Philippe (Swiss Journal of Sociology)
Higher education is a site of contesting visions by actors in politics, science and the economy. This article investigates imaginations of the future articulated around the introduction of data science in Swiss higher education through a qualitative analysis of study programmes, policy documents, and business reports. Universities envision data sciences mainly in reference to economic and technological concepts, which contribute to the coordination of the various actors and thus unfolds specific performative effects in the present.